Zearalenone Blocks Autophagy Flow and Induces Cell Apoptosis During Embryo Implantation in Gilts. (1st April 2020) - Wu, Lihang; Duan, Qianni; Gao, Dengying; Wang, Yueying; Xue, Songyi; Li, Wenchao; Lei, Minggang
Abstract: Zearalenone (ZEA) has been proved to be toxic, particularly to the reproductive system of gilts. The effect of ZEA on gilts during embryo implantation window period is of particular interests. Here, we observed window stage dysontogenesis of gilts treated with ZEA. In endometrial tissues and cells, autophagosomes increased significantly and mitochondria were damaged with increasing ZEA concentration. Addition of autophagy inhibitor confirmed that ZEA blocks the autophagic flow in the fusion of autophagosomes and lysosomes. In conclusion, ZEA exposure during embryo implantation results in endometrium inflammation by activating autophagy while blocking autophagy flow at the same time, leading to the significant accumulation of autophagosomes. The aforementioned effects of ZEA induce the apoptosis of primary endometrial cells through the caspase3 pathway, which would break the uterus environment balance and finally lead to embryo implantation failure and dysontogenesis in gilts.